Is anything left of the ‘Keynesian revolution’? (2007)
The conduct of British fiscal policy has changed during the post-war period, reflecting both the pressure of events and the evolution of thinking about macroeconomic policy. This essay reviews the changes in policy approach and relates them to the ultimate objectives of macroeconomic policy. Two objectives are usually emphasized, high (or full) employment and price stability, although equilibrium in external payments and economic growth are sometimes also mentioned.